Effects of Workplace Supervised Exercise on Psychological Capital: An Intervention Study - Carmen M. Salvador-Ferrer; Pedro A. Diaz-Fúnez; Álvaro Carrera-Ruiz; Montserrat Monserrat-Hernández; Enrique G. Artero; Miguel A. Mañas-Rodríguez (Sports)
Public employees face a growing array of professional challenges, and psychological capital (PC) has emerged as a valuable resource to address them. Workplace supervised exercise (WSE) programs can improve physical fitness and personal resources, though their adoption in organizations is limited. This study examines the impact of a long-term WSE program on the psychological capital of public administration employees. Fifty-five participants completed PC questionnaires and attended at least 40% of the sessions; 49.1% were women, and 40% were over 50 years old (age range: 24–73 years). A quasi-experimental design without a control group was used with a longitudinal design, and a nine-month WSE program (from October to June) was implemented. The data show gender-specific variations in PC patterns. Among men, incremental increases were observed over the three measurement intervals, with statistical significance achieved only in self-efficacy and hope. Among women, an upward trend was observed between October and February without statistical significance, followed by a slight decline. The results suggest that the WSE program may enhance personal resources, particularly hope and self-efficacy, highlighting the importance of tailoring WSE programs to the specific characteristics of the target group.